Does the Amended Audit Report Minimize the Audit Expectation Gap? Evidence from Bangladesh - Akther, Taslima; Moniruzzaman, Mohammad; Gutiérrez, Ana Licerán (Dhaka University Journal of Business Studies, 2026)
The purpose of this study is to investigate the impact of using the ISA 700 (Revised) amended audit report on minimizing the Audit Expectation Gap (AEG). A total of 189 respondents completed a questionnaire distributed to auditors and two audit report user groups, including credit analysts and non-professional capital market investors with beneficiary owner (B/O) accounts. The Mann-Whitney-U test, a non-parametric test, was used to compare the means of two independent samples and to determine the audit expectation gap. According to the findings of this study, the amended audit report reduces the unreasonable audit expectation gap in terms of auditors' general responsibilities, auditors' responsibilities for fraud detection, audit report meaning and usefulness, and, to a lesser extent, auditors' responsibility for going concern assessment. The explicit information in the ISA 700 (Revised) amended audit report creates another expectation gap regarding auditors' responsibility for other information, known as a reasonable standard gap. This study's theoretical contribution is that it confirms that the expansion of audit report and revision of audit standards affect the audit-related expectation gap among users. Users are aware of the revision; however, the impact varies depending on the users' desire, knowledge, and frequency of reading and using the audited financial statements. As the AEG is regarded as a driving force behind relentless reform in audit regulation; despite that an unjustified reform may result in no benefits to users. Thus, this research provides guidance to audit practitioners and audit regulators on the rationalization of reform in audit reports, such as the ISA 700 (Revised) audit report. This study is the maiden to explore the impact of using a revised audit report following the adoption by the Institute of Chartered Accountants of Bangladesh (ICAB) and also by the Financial Reporting Council (FRC) on minimizing the AEG in Bangladesh. The study's geographical focus is on audit regulators and practitioners in developing countries, who can benefitted from new insights into the role of adopting continuous improvement in auditing standards and reporting practices. Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 1-29